Development of muscle weakness in a mouse model of critical illness: does fibroblast growth factor 21 play a role? - Wouter Vankrunkelsven; Steven Thiessen; Sarah Derde; Ellen Vervoort; Inge Derese; Isabel Pintelon; Hanne Matheussen; Alexander Jans; Chloë Goossens; Lies Langouche; Greet Van den Berghe; Ilse Vanhorebeek (Skeletal Muscle, 2023)
Abstract Background Critical illness is hallmarked by severe stress and organ damage. Fibroblast growth factor 21 (FGF21) has been shown to rise during critical illness. FGF21 is a pleiotropic hormone that mediates adaptive responses to tissue injury and repair in various chronic pathological conditions. Animal studies have suggested that the critical illness-induced rise in FGF21 may to a certain extent protect against acute lung, liver, kidney and brain injury. However, FGF21 has also been shown to mediate fasting-induced loss of muscle mass and force. Such loss of muscle mass and force is a frequent problem of critically ill patients, associated with adverse outcome. In the present study, we therefore investigated whether the critical illness-induced acute rise in FGF21 is muscle-protective or rather contributes to the pathophysiology of critical illness-induced muscle weakness. Methods In a catheterised mouse model of critical illness induced by surgery and sepsis, we first assessed the effects of genetic FGF21 inactivation, and hence the inability to acutely increase FGF21, on survival, body weight, muscle wasting and weakness, and markers of muscle cellular stress and dysfunction in acute (30 h) and prolonged (5 days) critical illness. Secondly, we assessed whether any effects were mirrored by supplementing an FGF21 analogue (LY2405319) in prolonged critical illness. Results FGF21 was not required for survival of sepsis. Genetic FGF21 inactivation aggravated the critical illness-induced body weight loss (p = 0.0003), loss of muscle force (p = 0.03) and shift to smaller myofibers. This was accompanied by a more pronounced rise in markers of endoplasmic reticulum stress in muscle, without effects on impairments in mitochondrial respiratory chain enzyme activities or autophagy activation. Supplementing critically ill mice with LY2405319 did not affect survival, muscle force or weight, or markers of muscle cellular stress/dysfunction. Conclusions Endogenous FGF21 is not required for sepsis survival, but may partially protect muscle force and may reduce cellular stress in muscle. Exogenous FGF21 supplementation failed to improve muscle force or cellular stress, not supporting the clinical applicability of FGF21 supplementation to protect against muscle weakness during critical illness.